Muscle coordination in cross-country skiing: The effect of incline on the v2-skate technique - Brown, W. J.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study examined differences In upper (UB) and lower-body (LB) muscle activation of twelve elite Nordic skiers using the V2-skate at two inclines via electromyography (EMG). Subjects roller-skied on a treadmill for two 2-minute bouts, one at moderate grade - high speed and one at steep grade - low speed to keep heart rate equal between bouts. EMG was recorded (1 O-second interval), normalized to maximal isometric voluntary contraction, and analyzed for cycle time, peak and average activation, and within-cycle times for activation onset, offset, and peak activation of each muscle. UB tended to remain active for a longer proportion of the cycle at steeper grades while the opposite was true of LB. UB may play an increased role in the V2-skate at steeper grades independent of intensity, although no significant difference in LB or UB response to grade was found (p < 0.05).